SMART education technologies in mathematics teacher education - ways to integrate and progress that follows integration. (2nd January 2020) - Galimullina, Elvira; Ljubimova, Elena; Ibatullin, Rinat
ABSTRACT: SMART Education Technologies (SET) are already in place to provide teachers with different software packages and technologies to facilitate their teaching. However, when it comes to mathematics teaching in Russia, the situation here is different as the articulation of such SET in the Russian context is inadequate. This study redefines mathematics teacher education with smart technologies and identifies IT competencies that are needed to cope with the redefined curriculum. The designed course programme was implemented in the Elabuga Pedagogical Institute, involving 7 teachers from the Institute, 123 students (trainee teachers) and 5 schoolteachers (experts) to keep a professional eye on the learning experience. To evaluate the effectiveness of the curriculum, a survey was carried out among teachers and experts. The survey questionnaire captured the progress made in competence development alongside three modules. The progress that students were making throughout the course was evaluated at the 'mock teaching' lesson, where students presented their individually prepared parts of a lesson on a given topic using Information and Communication Technologies (ICT). The way the learning process was organised encouraged students to use various software packages to handle maths-related problems. The research results showed that the SET learning path was flexible and allowed modification of the instructional strategy to better meet the needs of individual learners.